Transformations of the Employment Structure as an Expression of the Transformation of Polish Industry Against the Background of the European Union - Rachwał, Tomasz (Bulletin of Geography. Socio-economic Series, 2011)
Global social and economic changes, connected mainly with globalization processes, have an impact on changes both in present spatial and division structures of the industry and in its functions in the economic development of various spatial systems. The aim of the paper is to analyze changes in the industry's role in the Polish economy during the period of economic transformation and European integration based on its share in the employment structure. These changes are set against transformations in other EU countries, diversification and transformations of the division structure of employment in Polish industry and the similarity of the Polish employment structures to the EU countries as an expression of transformation processes. The analyzed processes are stimulated by the international environment and a change in national conditions for the socio-economic development.